EKSPRESI WAJAH DALAM KARYA LUKIS SURREALIS - TEZAR MAAS PUTRA, Drs. Erfahmi, M.Sn., Dra. Zubaidah, M.Pd. (Universitas Negeri Padang, 2016)
An artist always felt the anxiety in her that an accumulation of circumstances surrounding the response. Anxiety is what is the forerunner to the birth of a masterpiece. In life, many methods are used to establish a social relationship, one of which is done by interacting through communication. Communication and expression are two very related. Facial expression is a form of nonverbal communication, and can convey the emotional state of a person to those who observe it.Facial expression in painting surrealism pouring works ideas are actually centered on the human mindset that is, from observations made by the man himself.Performers can see, observe, learn, experience, understand, appreciate, think, behave, behave calmly to the natural and social environment of their own as well as those outside of themselves.These works are created through various processes and from the author's own experience in life. Reference the author collected in the form of pictures, books, art magazines, exhibition catalogs, direct observation, data collection and information in the field in the form of opinions and suggestions, and some painters both national and international level as a reference as well as motivation.Final Project, the production work of selecting those which are well known as a symbol of expression in the work of surrealist painting.Human beings have a nature as social beings, so that men are required to interact with each other to establish a harmonious life in society. In the sociable man should be able to read other people's facial expressions in order to avoid misunderstandings that could eventually cause problems. Because, basically, human social life would not be much of a problem, just how people react to it.Keyword : Painting, Surrealism